Safety of Iron Fortification and Supplementation in Malaria-Endemic Areas - Brittenham, Gary M. (Nestle Nutr Inst Workshop Ser, 2012)
This review considers the safety of iron supplementation and fortification for the prevention and correction of iron deficiency in malaria-endemic areas, with a focus on potential means whereby provision of additional iron might heighten the risks of malaria and other infections. Iron deficiency itself may increase the risk of morbidity and mortality from malaria and other infections. The available evidence indicates that iron interventions are safe in settings without endemic malaria, and, with adequate health care, in regions with high transmission of malaria and other infections. Without regular surveillance and treatment of malaria and other infections, iron supplementation of individuals who are iron deficient seems safe, but individuals who are iron replete may have an increased risk of adverse outcomes. The mechanisms responsible for harmful effects with iron supplementation have not been established. These are likely to include the effects of (a) increased amounts of absorbed iron, with the production of plasma non-transferrin-bound iron, (b) increased amounts of iron in the gastrointestinal tract, with effects on gastrointestinal structural integrity and on gut microflora, and (c) the complex immune effects of iron interventions. Iron fortification appears to be generally safe, although more data from malaria-endemic areas are needed.